What Americans Really Want . . . Really : the truth about our hopes, dreams, and fears - Luntz, Frank I. (New York : Hyperion, 2009)
The author of the bestselling "Words That Work" examines what Americans say they want, how their actions often contradict those claims, and what that means for businesses.
Includes bibliographical references (p. [291]-293) and index.
Keywords: Social psychology -- United States; Public opinion -- United States; Consumption (Economics) -- United States; National characteristics, American